GENEALOGY OF CONSERVATION NGOs ON THE ESTABLISHMENT OF THE AMBEL-MA'YA TRIBE CONSERVATION AREA IN RAJA AMPAT - George Mentansan; I Ketut Ardhana; I Nyoman Suarka; I Nyoman Dhana (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2021)
This article aims to reveal the genealogy of the International Conservation NGO towards the establishment of the Ambel-Ma'ya tribal conservation area so that the Ma'yalibit Bay conservation area in Raja Ampat is formed as well as a departure station for the establishment of other conservation areas in Raja Ampat. The research approach uses a Cultural Studies approach with descriptive qualitative research methods and slices of theory used, namely, the genealogy of practice and power from Michel Foucault.The results showed that before international conservation NGOs operated in Raja Ampat, they recruited actors and agents who were recruited from intellectuals of the Ma'ya indigenous peoples' institutions and religious and traditional leaders. Conservation NGOs act as captains as well as organic intellectuals and traditional intellectuals for the Ambel-Ma'ya tribe in the Ma'yalibit Bay of Raja Ampat acting as sea commanders in the boat of conservation ideology. Conservation NGOs are hiding behind the discourse of knowledge about high marine tropical biodiversity and the threat of its degradation as a result of the fishing behavior of fishermen who are not environmentally friendly, becoming the basis for discourse on knowledge, articulation and practice of language texts and capital of power to carry out discursive practices in the formation of conservation areas on tribal waters stage. Abel-Ma'ya. Keywords: Genealogy, NGO, Conservation, Ambel-Ma'ya, Raja Ampat